2021
DOI: 10.1177/15248399211033308
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Health of Migrant and Seasonal Farmworkers in the United States: Identifying Gaps in the Existing Literature, 2021

Abstract: There are profound health inequities for agricultural workers. We sought to assess the literature on migrant and seasonal farmworker health with an eye toward health promotion interventions, special populations, use of community health workers (CHWs), and technology. We conducted a systematic mapping review by searching five databases in March 2021. Using quantitative content analysis after establishing interrater reliability, we coded titles and abstracts to assess 13 topics and six characteristics of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…The literature on migrant and seasonal farmworker health has limited information on the resources available to CHWs in their work to provide critical health education and information to farmworkers [ 2 , 8 ]. This dearth may be due, in part, to the lack of a formalized position for CHWs, which would acknowledge the complex responsibilities CHWs assume in providing both social and health-enabling services to farmworkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on migrant and seasonal farmworker health has limited information on the resources available to CHWs in their work to provide critical health education and information to farmworkers [ 2 , 8 ]. This dearth may be due, in part, to the lack of a formalized position for CHWs, which would acknowledge the complex responsibilities CHWs assume in providing both social and health-enabling services to farmworkers.…”
Section: Discussionmentioning
confidence: 99%
“…Farmworker-serving CHWs in North Carolina (NC) tend to be female, Spanish-speakers, and Latinx [ 7 ]. Whereas CHWs serve an important role in providing health care access and enabling services (e.g., health education, interpretation, and case management) for farmworkers, CHWs have received limited attention in the literature [ 8 ]. Furthermore, our previous research involving farmworker-serving CHWs has demonstrated they have limited access to farmworker health research findings and other important health information resources [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic data in the USA show that migrant farmworkers leave their homes every year to work in the fields in the USA, return to their countries and come back again the next year and are likely to amplify exposure to C. cayetanensis oocysts through contact with contaminated environmental vehicles. Most migrant farm workers live in substandard conditions, and nearly two-thirds of them live in poverty [ 56 , 57 ]. Racial residential segregation is a fundamental cause of differences in health status because it shapes socioeconomic conditions for non-white populations at the individual, household, neighborhood, and community levels, can create social and physical risks in residential environments that adversely affect health [ 53 , 54 ], and could support infectious diseases such as cyclosporiasis.…”
Section: Cyclosporiasis Situation In Epidemic Areas: Potential For En...mentioning
confidence: 99%
“…Their low wages put them at risk for chronic poverty and food and housing insecurity. They often experience multiple marginalized identities, such as being Latinx and lacking documentation to live in the United States legally, which can cause prolonged stress (Bloss et al, 2022). Individuals who lack legal documentation status experience social and economic barriers, such as low wages and fear of deportation, which place them at risk for health issues (Cabral & Cuevas, 2020).…”
mentioning
confidence: 99%